ELECTRICALLY CONDUCTIVE FILMS - CHARACTERISATION OF WEIGHT-REDUCED POLYMER FILMS FOR USE IN A BIPOLAR LITHIUM-SULPHUR BATTERY - Engelke, Martin; Hickmann, Thorsten Manfred; Krause, Beate (International Journal of Engineering Science Technologies, 2025)
With a theoretical energy density of around 2600 Wh kg-1 and a specific capacity of approx. 1675 mAh g-1, the lithium-sulphur battery (Li-S battery) is a promising technology for future energy storage solutions. Lithium-sulphur batteries currently achieve specific energy densities of between 400 and 600 Wh kg-1 in practical applications, making them an attractive alternative to lithium-ion batteries. Despite their advantages, technical challenges such as the dissolution of polysulphides in the electrolyte and the low cell voltage are significant obstacles to the commercialisation of this technology. In the "BiPoLiS" project (development of lithium-sulphur bipolar batteries), these challenges are addressed by combining lithium-sulphur battery technology with a previously undescribed bipolar structure. The focus of this article is on the development of weight-reduced polymer conductor foils, which should contribute to an improved battery packing density due to the planar layer structure - compared to single cells. Experimental investigations were carried out to develop an electrically conductive, flexible and weight-reduced film suitable for use in lithium-sulphur batteries. The investigations were based on compounds of styrene-ethylene-butylene-styrene (SEBS) and polypropylene (PP), whereby various mixing ratios were tested. The optimum mixture was found with a ratio of a SEBS compound to a PP compound of 30:70, which had an electrical in-plane conductivity of around 346 S m-1 and a through-plane conductivity of around 60 S m (-1). The flexible film was produced using a calendering process, whereby a thickness of approx. 0.2 mm was achieved. Thanks to the innovative combination of bipolar design and polysulphide-free sulphur cathode, the lithium-sulphur battery can offer significant advantages in terms of energy density and manufacturing costs. This technology could play a decisive role, particularly in the field of electromobility and industrial energy storage. Future work should focus on optimising the process parameters for reducing the film thickness and investigating the long-term stability in order to exploit the full potential of these new materials and enable their commercial applications.